Application of phage-display developed antibody and antigen substitutes in immunoassays for small molecule contaminants analysis: A mini-review. (1st March 2021) - Zhao, Fengchun; Shi, Ruirui; Liu, Ruxia; Tian, Yuan; Yang, Zhengyou
Highlights: Toxic small-molecule contaminants (SMCs) in food pose a potential risk to food safety. Phage-display is widely used to prepare substitutes of SMCs' antibodies and antigens. Five types of substitutes developed by phage-display are summarized. Application forms of these substitutes in immunoassays for SMCs are reviewed. Abstract: Toxic small molecule contaminants (SMCs) residues in food threaten human health. Immunoassays are popular and simple techniques for SMCs analysis. However, immunoassays based on polyclonal antibodies, monoclonal antibodies and chemosynthetic antigens have some defects, such as complicated preparation of antibodies, risk of toxic haptens using for antigen chemosynthesis and so on. Phage-display technique has been proven to be an attractive alternative approach to producing antibody and antigen substitutes of SMCs, and opened up new realms for developing immunoassays of SMCs. These substitutes contain five types, including anti-idiotypic recombinant antibody (AIdA), anti-immune complex peptide (AIcP), anti-immune complex recombinant antibody (AIcA) and anti-SMC recombinant antibody (anti-SMC RAb). In this review, the principle of immunoassays based on the five types of substitutes, as well as their application and advantages are summarized and discussed.